Auditoría de gestión y su impacto en la toma de decisiones del cuerpo de bomberos del cantón Valencia provincia de Los Ríos año 2020. - Cepeda Morales, Marjorie Estefania (2021)
This research proposes a management audit to the public institution Fire Department of the canton Valencia, which aimed to identify deficiencies or failures in internal control, this way strategies planned to obtain findings and reliability of processes in the institution, to carry out the proposed research methodology used: quantitative, qualitative, bibliographic and field research, as well as inductive, deductive, descriptive methods and the technique of the interview to the manager, general information was obtained from the institution through the application of internal control through the COSO I and management indicators. The contributions of the research were of great importance because the audit gave as results a risk level of 54% to send out an erroneous opinion according to the current situation of the institution. The lack of a manual of policies and procedures, the staff can perform their duties should be noted that the results made known through the findings sheet, decision-making matrix, and in the final performance audit report reflecting their strengths and weaknesses, with the implementation of policies and procedures manual detailing the activities for each workplace and avoiding duplication of functions.